Identification of Types and Analysis of Microplastic Content in Fresh Shrimp Marketed in Dumai City - Irene Dwi Rani Br Lingga; Bintal Amin; Efriyeldi Efriyeldi (Jurnal Perikanan dan Kelautan, 2026)
Microplastics are plastic particles smaller than 5 mm that are difficult to remove from the ocean. This study aimed to identify the types and levels of microplastics found in vannamei (Litopenaeus vannamei) and white shrimp (Penaeus merguiensis) marketed in Dumai City, conducted from September to November 2025. The method used was a survey, and the research locations were determined using purposive sampling. Vannamei shrimp samples were collected from Bundaran Market, and white shrimp from Dumai City Fish Landing Site (TPI), and analyzed at the Marine Chemistry Sciences of the Department of Marine Sciences, Faculty of Fisheries and Marine Sciences, Universitas Riau. The results of this study indicate that three types of microplastics were present in both shrimp species: fibres, fragments, and films. Statistical analysis further revealed that the microplastic content in both shrimp species across different sizes did not differ significantly (p > 0.05). There were no significant differences in microplastic content between vanamei and white shrimp (p > 0.05). The results of linear regression analysis between microplastic content and shrimp morphometric measurements revealed a weak relationship